Design and Construction of Semiconductor Laser Range Finder for Target Designation - Hussein, M. T.; Hafidh, Z. A.; Ali, B. R. (Iraqi Journal of Laser, 2004)
The aim of this research is to design and construct a semiconductor laser range finder operating in the near infrared range for ranging and designation. The main part of the range finder is the transmitter which is a semiconductor laser type GaAs of 0.904 mm wavelength with a beam expander, and the receiver with its collecting optics. The characteristics of transmitter pulse width were 200ns and threshold current 10 Amp. and maximum operating current 38 Amp. The repetition rate was set at 660 Hz and maximum output power about 1 watt. The divergence of the beam was 0.268o. A special computer code was used for optimum optical design and laser spot size analysis and for calculation of atmosphere attenuation.